2014
DOI: 10.1016/j.otsr.2014.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of scapular pillar anatomy on scapular impingement in adduction and rotation after reverse shoulder arthroplasty

Abstract: III, experimental study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Previous studies have demonstrated that postoperative active ROM was determined by numerous factors. The type of implant, 5 , 17 , 30 the morphology of the scapula, 31 and pre-, 32 , 33 intra-, 34 and postoperative 16 , 21 soft tissue considerations are known to be contributors. The present study revealed that the type of impingement induced by the reverse design is another key element.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that postoperative active ROM was determined by numerous factors. The type of implant, 5 , 17 , 30 the morphology of the scapula, 31 and pre-, 32 , 33 intra-, 34 and postoperative 16 , 21 soft tissue considerations are known to be contributors. The present study revealed that the type of impingement induced by the reverse design is another key element.…”
Section: Discussionmentioning
confidence: 99%
“…This is important as changes related to human scapular morphology, such as scapular neck or critical shoulder angles, also impact the tendency towards impingement. 31 However, the number of specimen did not allow for the comparison of the different sizes of glenospheres. Another limitation of this study is the partial omission of the humeral sided wear.…”
Section: Discussionmentioning
confidence: 99%
“…This unique morphological study prevented us from analyzing patient-related factors that may impact post-operative ROM. Normal or pathologic changes related to human scapular morphology may also lead to significant differences [24]. Another limitation of this study is the omission of soft tissue tension which can restrict ROM, particularly in revision or post-traumatic cases.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…Few studies have examined scapular morphology related to RSA and scapular notching (Table ). Simovitch et al () introduced the concept of SNA measurement that was later reproduced by Berhouet et al (), Sabesan et al (), Fortun et al () and by this study. Comparison can be seen in Table .…”
Section: Discussionmentioning
confidence: 52%